Plant-Derived Nanoparticles: A Green Approach for Drug Delivery Systems - Dr.Prem Kumar Gautam; Dr. Seema Narkhede; Dr. Subash Chandra Sahu; Dr. Pamil Tayal; Mrs. Marina Albuquerque; Dr. Tejaswini Prasad Babar (Revista Electronica de Veterinaria, 2024)
In recent years, the intersection of nanotechnology and plant sciences has opened new avenues for developing innovative drug delivery systems. Plant-derived nanoparticles (PDNPs) offer a sustainable, eco-friendly alternative to synthetic nanomaterials, characterized by their biocompatibility, biodegradability, and low toxicity. These nanoparticles, synthesized using natural plant extracts, not only mitigate the environmental impact associated with conventional nanoparticle production but also enhance the therapeutic efficacy of encapsulated drugs. This paper reviews the current advances in PDNPs, focusing on their synthesis, characterization, and application in drug delivery systems. The potential of PDNPs to revolutionize drug delivery is explored through a discussion of their advantages over traditional methods, challenges in their development, and future perspectives. The integration of green chemistry principles with nanotechnology underscores the importance of PDNPs in the evolution of safe and effective drug delivery mechanisms. The application of nanotechnology in drug delivery systems has revolutionized the pharmaceutical landscape, offering innovative solutions to overcome the limitations of traditional therapeutics. Plant-derived nanoparticles (PDNPs) represent a significant advancement in this domain, aligning with the principles of green chemistry and sustainable development. These nanoparticles are synthesized using bioactive compounds found in plant extracts, which act as natural reducing and stabilizing agents. The synthesis process of PDNPs is not only environmentally friendly but also cost-effective, eliminating the need for hazardous chemicals and high-energy inputs.PDNPs exhibit unique physicochemical properties, such as controlled size distribution, high surface area, and versatile surface chemistry, which are critical for enhancing drug bioavailability and ensuring targeted delivery. The encapsulation efficiency of drugs within PDNPs can be finely tuned by manipulating factors such as pH, temperature, and the concentration of plant extracts, enabling the design of nanoparticles with specific therapeutic profiles. Furthermore, PDNPs offer the advantage of biodegradability, ensuring that the nanoparticles are safely metabolized and excreted from the body without accumulating in tissues, thus minimizing potential toxicity. The structural integrity and functionalization potential of PDNPs allow for the attachment of various ligands, antibodies, or peptides, facilitating site-specific targeting of therapeutic agents. This targeted approach not only enhances the therapeutic index of drugs but also reduces off-target effects, thereby improving patient outcomes. Additionally, the inherent antioxidant, anti-inflammatory, and antimicrobial properties of certain plant-derived compounds can be leveraged to synergistically enhance the therapeutic effects of the encapsulated drugs. This paper delves into the detailed mechanisms underlying the synthesis of PDNPs, the characterization techniques employed to assess their structural and functional attributes, and their application in delivering a broad spectrum of drugs, including chemotherapeutics, antibiotics, and anti-inflammatory agents. We also explore the challenges associated with the large-scale production of PDNPs, including issues related to batch consistency, nanoparticle stability, and the regulatory landscape. The potential of PDNPs to revolutionize the field of drug delivery is underscored by their ability to integrate therapeutic efficacy with environmental sustainability, making them a promising candidate for future pharmaceutical applications.